Design and validation of theory-based perceptions concerning the physical literacy questionnaire for pregnant women (P2LQ-PW) - Leila Kianfard; Shamsaddin Niknami; Farkhondeh Amin Shokravi; Sakineh Rakhshanderou (BMC, 2022)
Abstract Background There is evidence that physical literacy plays an essential role in understanding the importance of maintaining appropriate physical activity and thereby preventing illnesses during pregnancy. The present study aimed to design and validate a physical literacy questionnaire focused on pregnant women. Methods In this exploratory psychometric study, theory-based perceptions concerning the physical literacy questionnaire for pregnant women were designed. Face-to-face interviews were conducted to develop the initial items. The findings from the interviews were merged with the literature review. The content, construct, and face validity was assessed by the participation of midwives, health educationists, and pregnant women. The content validity ratio, content validity index, and impact score of the items were calculated. The construct validity of the questionnaire was calculated through confirmatory and exploratory factor analysis. The reliability of the questionnaire was calculated by the standard error of measurement, intra-class correlation coefficient, composite reliability, and Cronbach's alpha. Results The highest score was seen in the knowledge subscale and the value of Cronbach's alpha for the subscales was 0.89 to 0.97, and the value of ICC was 0.76 to 0.89. The correlation according to the opinion of experts was satisfactory in all items of the questionnaire. The minimum loading factor for varimax rotation in the knowledge subscale was 0.41, the attitude was 0.56, the nurture factor was 0.38, and enabling factor was 0.27. The compatibility of the model among the constructs was confirmed by the normed chi-square (χ2/ df) < 5.0, comparative fit index ≥0.90, Tucker-Lewis index ≥0.9, and root mean square error of approximation < 0.08. Conclusion The physical literacy questionnaire for pregnant women is the first tool based on the PEN-3 model that other researchers can use to collect data and conduct educational interventions to change physical literacy behavior among Persian women during pregnancy.